Fatima Marian Apparition and TGD inspired theory of consciousness - Pitkänen, Matti (2019)
A TGD (Topological Geometrodynamics) based model for the Fatima Marian apparition (FMA) is discussed. The notion of many-sheeted space-time implies the notion of magnetic body (MB). TGD based view about dark matter predicts mechanisms making possible quantum coherence in macroscopic and even astrophysical scales. TGD inspired theory of consciousness relying on the notion of zero energy ontology (ZEO) predicts entire hierarchy of conscious entities (selves) so that the notion of collective consciousness makes sense. One ends up to a general model of remote mental interactions proposed to be used routinely in the communica-tions (say EEG) between personal MB and biological body (BB) in terms of dark photons. Sensory representations, realized in TGD universe at MB in-volve in an essential manner the sharing of mental images identifiable as sub-selves of self. The model explains UFO and ET experiences as telepathic experiences, in which primitive plasmoid like life forms (apparent UFOs) using microwaves as their metabolic energy source - “food” - serve as “mediums” entangling the experiencer with magnetospheric or even extraterrestrial conscious entities. If this entity can be assigned to magnetosphere, one can understand why tectonic activity and perturbations of the Earth’s magnetic field correlate with UFO and ET experiences. The same conceptual framework provides models of homeostasis, homeopathy, endogenous realization of intentions, and remote mental interactions such as telepathy, and psychokinesis. The basic mechanism explains also many anomalous phenomena claimed by free energy researchers. In the case of FMA the well-documented effects - in particular, the strange buzzing sounds heard by the witnesses and explainable in terms of microwave hearing - lead to a rather detailed model in which “Marian” could be identified as conscious entity representing collective level of consciousness.